COMPARTMENTALIZATION AND GEOMORPHOLOGICAL EVOLUTION OF THE CUIABA RIVER FLOODPLAIN, MATO GROSSO, PANTANAL - Meira, Fabiana Cristina [UNESP]; Stevaux, Jose Candido; Torrado, Pablo Vidal; Assine, Mario Luis [UNESP] (Uniao Geomorfologia Brasileira, 2019)
The Cuiaba River watershed, located in the state of Mato Grosso, drains an area of approximately 36,000 km(2). When it enters the Pantanal area in Mato Grosso, the Cuiaba river starts depositing the sediments transported from its plateau, forming a complex of plains and setting up an extensive fluvial megafan with an area of 14,580 km(2). This study comprises a confined plain with 1.850 km(2) which is inserted in the proximal section of that megafan, henceforth called 'contained plain', since it is located among higher terrains. This work intended to understand the evolution of this plain based on its geomorphological compartmentation. The plain of the Cuiaba river was compartmentalized into seven units: 1) Meanders Plain with Structural Control (PMCE); 2) Belt Meanders Old Cuiaba (ADCC); 3) Belt Meanders Cuiaba Modern (CMCM) 4) System Plain Old Anabranching (PSAA); 5) System Plain Anabranching with Disruption of Ponds (PSALR); 6) System Plain Anabranching with Control Lito-Structural (PSACLE); 7) Current Plain Superimposed on Anabranching Old System (PASSAA). The deposits of these units ranged from clay to coarse sand with gravel. In some compartments there were significantly extended litoplintic layers. Datings for C-14 and LOE reported ages between C-14 8,710 +/- 30 cal years BP and LOE 260 +/- 30 years BP. At the beginning of the Holocene, the Cuiaba River had a meandering channel pattern on its whole extention. From 8,710 years BP avulsions occurred and caused the system migration to SW, and the fluvial system acquired an anabranching pattern. Around 5,530 years BP, due to the low sedimentation rate, the plain suffered pedogenesis with the posterior development of a litoplintic layer which spreads itself into multiple compartments, especially those in the sector where the river has got the anabranching pattern, the genesis of litoplintic layers is linked to water deficit. The current position of the main channel of the Cuiaba river dates from about 2,250 years BP. The analysis's results, associated with bibliographical researches, point to a climate change, from humid to dry, that occurred around 5,000 years BP, coinciding with the age of that litoplintic layer; however, we can observe that the change of the river pattern from meandering to anabranching started around 8710 years BP, showing that there is no relationship between those two changes. Currently the river keeps an anabranching pattern, evolving and moving towards a sector in which the litoplintic layer is broken, affecting the layout of the river and functioning as the local base level.
Keywords: Morphotectonic; Litho-Structure; Remote Sensing